A Notorious Mimicker Nasal Melanoma: A Case Report - Bastakoti, Shankar; Gautam, Dej Kumar; Upreti, Suraj Raj; Jha, Nandita; Dhungana, Ishan (Annapurna Journal of Health Sciences, 2023)
Melanomas arising in the nasal cavity or paranasal sinus are rare and have a poor prognosis and is more aggressive than cutaneous counter part. The incidence rate reaches its peak when the patients are in the 5th to 8th decades of life, and the disease is slightly more common in males than females; age and sex do not affect the prognosis. We present a case with histologically deceiving features which was proven Malignant Melanoma by application of Immunohistochemistry. On sinoscopic examination, a mass noted of which incisional biopsy was obtained. Histologically, poorly differentiated Sinonasal carcinoma and Malignant Vascular Neoplasm was differential diagnosis. On immunohistochemistry, strong expression of SOX-10, Melan-A, HMB-45 was observed and p63, CK-7, CK20, Synaptophysin, CD56, CD138, CD45, S100, Desmin, Myogenin were all non-immunoreactive. Thus Malignant Melanoma was final diagnosis.Awareness of melanoma mimickers is very important for clinicians in general, and pathologists in particular. Further immunohistochemistry should be utilized whenever neoplasm with grey zone histomorphology is encountered.